Armenia, Azerbaijan and Georgia relations with Israel in the context of the October 7, 2023 Hamas attack - Kardaś, Jarosław (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2024)
The main purpose of this article is to analyze the relationships of Armenia, Azerbaijan, and Georgia with Israel in the context of the Hamas attack on October 7, 2023. Although Armenia, Azerbaijan, and Georgia are geographically situated outside the Middle East and are part of the former USSR region, they closely monitor developments in the neighboring Middle East area. Examining the attitudes of the three South Caucasus countries aims to address whether the authorities of the three countries reacted similarly to the latest episode of the Israeli-Palestinian conflict, or if notable differences emerged. This analysis will help determine the current state of relations between Israel and Armenia, Azerbaijan and Georgia, as well as assess whether any of the South Caucasus republics can be considered a loyal ally of Israel in the region. Głównym celem niniejszego artykułu jest przeanalizowanie stosunków Armenii, Azerbejdżanu oraz Gruzji z Izraelem w kontekście ataku Hamasu z 7 października 2023 r. Mimo iż Armenia, Azerbejdżan oraz Gruzja nie są zaliczane do regionu Bliskiego Wschodu (a do tzw. obszaru byłego ZSRR), to jednak bardzo uważnie obserwują procesy zachodzące na sąsiadującym obszarze. Zbadanie postawy trzech państw zakaukaskich wynika z chęci poszukania odpowiedzi na pytanie, czy władze wszystkich trzech wymienionych wyżej krajów podobnie zareagowały na kolejne rozmrożenie konfliktu izraelsko-palestyńskiego, czy może jednak występowały w tym zakresie pewne różnice. Pozwoli to określić, jak współcześnie wyglądają relacje pomiędzy Izraelem a Armenią, Azerbejdżanem oraz Gruzją, a także to, czy którąś z republik Kaukazu Południowego można nazwać lojalnym sojusznikiem Izraela w tym regionie.
Relacje Armenii, Azerbejdżanu oraz Gruzji z Izraelem w kontekście ataku Hamasu z 7 października 2023 r.
Keywords: Countries of the South Caucasus; Israel; Hamas; attack; October 7; 2023; państwa Kaukazu Południowego; Izrael; zamach; 7 października 2023 r.